Coupling coordination of digital village construction and high-quality agricultural development in China - Yuan Tian; Yuxi Zhou (PLoS ONE, 2025)
This study aims to investigate the coupling coordination relationship between digital village construction and high-quality agricultural development in China, along with influencing factors, in order to provide policy recommendations for fostering the concurrent advancement of these two domains. Utilizing coupling coordination degree model, spatial econometric model and other methods, this paper analyzes the panel data of 31 provinces (municipalities and autonomous regions) in China spanning from 2011 to 2022. The key findings indicate the following: Firstly, there has been an overall enhancement in the levels of digital village construction and high-quality agricultural development across all Chinese provinces, with the eastern region exhibiting a higher developmental status compared to the central and western regions. Secondly, the coupling coordination degree has shown a collective improvement, albeit with variations in coordination levels among different regions; however, the regional disparities are gradually narrowing. Thirdly, the level of economic development and agricultural financial expenditure emerges as significant factors influencing the degree of coupling coordination, demonstrating not only direct positive effects but also positive spatial spillover effects. Finally, this study proposes recommendations to promote sustainable agricultural development, such as setting up agricultural technology innovation platforms, establishing digital agricultural production bases, and training farmers in digital skills in order to mitigate regional disparities and foster mutual advancement across all regions.